The Association of Aquaporins with MAPK Signaling Pathway Unveils Potential Prognostic Biomarkers for Pancreatic Cancer - da Silva, Inês V. (2025)
Funding Information: This research was funded by Funda\u00E7\u00E3o para a Ci\u00EAncia e Tecnologia (FCT), Portugal, grant 2022.06601.PTDC, researcher contracts 2022.03691.CEECIND to I.V.d.S. and DL57/2016 to P.A.L., and strategic project UID 04138\u2014Instituto de Investiga\u00E7\u00E3o do Medicamento (iMed.ULisboa). Publisher Copyright: © 2025 by the authors.